A Versatile and Efficient Plant Protoplast Platform for Genome Editing by Cas9 RNPs - Jiang, Wenzhi; Bush, Jenifer; Sheen, Jen (Frontiers in Genome Editing, 2021)
The ultimate goal of technology development in genome editing is to enable precisely targeted genomic changes in any cells or organisms. Here we describe protoplast systems for precise and efficient DNA sequence changes with preassembled Cas9 ribonucleoprotein (RNP) complexes in Arabidopsis thaliana, Nicotiana benthamiana, Brassica rapa, and Camelina sativa. Cas9 RNP-mediated gene disruption with dual gRNAs could reach ~90% indels in Arabidopsis protoplasts. To facilitate facile testing of any Cas9 RNP designs, we developed two GFP reporter genes, which led to sensitive detection of nonhomologous end joining (NHEJ) and homology-directed repair (HDR), with editing efficiency up to 85% and 50%, respectively. When co-transfected with an optimal single-stranded oligodeoxynucleotide (ssODN) donor, precise editing of the AtALS gene via HDR reached 7% by RNPs. Significantly, precise mutagenesis mediated by preassembled primer editor (PE) RNPs led to 50% GFP reporter gene recovery in protoplasts and up to 4.6% editing frequency for the specific AtPDS mutation in the genome. The rapid, versatile and efficient gene editing by CRISPR RNP variants in protoplasts provides a valuable platform for development, evaluation and optimization of new designs and tools in gene and genomic manipulation and is applicable in diverse plant species